1953
DOI: 10.1111/j.1365-2621.1953.tb17696.x
|View full text |Cite
|
Sign up to set email alerts
|

Roasting Time and Temperature Required to Kill Food Poisoning Microorganisms Introduced Experimentally Into Stuffing in Turkeys

Abstract: Bacterial food poisoning from poultry constitutes a considerable percentage of the total food poisoning outbreaks. Feig ( 7 ) stated that poultry was the vehicle of streptococcal infection "twice as frequently as meat, bakery products and potatoes." Poultry was further involved in 22% of 304 staphylococcic outbreaks and in 18.5 % of 54 salmonella outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1956
1956
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The temperature required to kill pathogenic microorganisms in turkeys and in stuffing has been studied by Castellani et al (1953), Wilkinson et al (1965), Bryan et al (1968), Echner et al (1988), and Lee (1993). In all cases it was reported that reaching 7°C, destroyed low levels of pathogenic bacteria in turkeys and turkey rolls, and 74°C was needed to achieve total pathogen destruction at the center of stuffing.…”
Section: Preparation Of Turkeys For Cookingmentioning
confidence: 99%
“…The temperature required to kill pathogenic microorganisms in turkeys and in stuffing has been studied by Castellani et al (1953), Wilkinson et al (1965), Bryan et al (1968), Echner et al (1988), and Lee (1993). In all cases it was reported that reaching 7°C, destroyed low levels of pathogenic bacteria in turkeys and turkey rolls, and 74°C was needed to achieve total pathogen destruction at the center of stuffing.…”
Section: Preparation Of Turkeys For Cookingmentioning
confidence: 99%
“…Coliforms and S. aureus were absent in all cooked chicken, indicating that temperature attained at the center was enough to destroy them. Castellani et al (1953) suggested that a temperature of 73.9C reached at the center of the stuffing during roasting of turkeys was sufficient to kill experimentally introduced organisms like Streptococci, Staphylococci and Salmonellae. Rogers and Gunderson (1958) observed that a center temperature of 71.…”
Section: Yeasts and Molds The Predictive Equation For Yeast And Moldmentioning
confidence: 99%
“…In roasting stuffed turkeys the internal final temperature of the center of the stuffing must reach 74° C for safety. 271 Castellani et al 272 evaluated final internal temperature for stuffed roasted turkeys. When roasted in an oven at 149° C the rates of heat penetration were about equal whether a moist or dry stuffing was used.…”
Section: Composition and Other Product Factorsmentioning
confidence: 99%